Propuesta de un plan estratégico basado en mobile marketing para difusión del patrimonio natural del cantón Pasaje. - Yarisigcha Hurtado, Carla Daniela; Sanmartin Cardenas, Nayeli Nicole (Machala : Universidad Técnica de Machala, 2024)
The purpose of this study is to show that the Pasaje canton has an exuberant natural heritage that requires further dissemination, especially for those natural attractions such as La Playita, Pailones de Muyuyacu and Pailones del Rio Tobar. According to the survey carried out using Microsoft Form, those are the ones that have fewer information or are hardly visited. Due to this, a strategic plan based on Mobile Marketing is proposed with the design of a prototype and preview of an application through Google Sites and AppCreator24, advertising campaigns with Google AdWords and dissemination through a WhatsApp channel by the name of "Rinconia Nature". The aforementioned strategies contribute to the development of local tourism in an innovative way. A mixed research approach was used for this study, combining quantitative and qualitative methods. Also, a descriptive type of research was used to understand the current situation of the problem and exploratory research to discover new aspects. It applies the deductive method to formulate and test hypotheses in order to optimise the Mobile Marketing strategy to promote the natural heritage of the Pasaje canton. It is concluded that there is a demand for information about the natural heritage of the Pasaje canton considering the outdoor activities that can be carried out there in a sustainable way. For this reason, it is important to emphasize the need for an effective dissemination strategy where the demographic profile of the sample supports the use of Mobile Marketing. Finally, it is recommended to develop an interactive mobile application, to integrate advertising campaigns in Google AdWords and WhatsApp, as well as to produce high quality visual content.
Este estudio tiene como propósito poner en evidencia que el Cantón Pasaje posee un exuberante patrimonio natural que requiere de una mayor difusión sobre todo para aquellos atractivos naturales como La Playita, Pailones de Muyuyacu y Pailones del Rio Tobar. De acuerdo con la encuesta realizada mediante Microsoft Form, aquellos son los que tienen menos información o son poco visitados. Debido a esto, se propone un plan estratégico basado en Mobile Marketing con el diseño de un prototipo y visualización previa de una aplicación por medio de Google Sites y AppCreator24, campañas publicitarias con Google AdWords y difusión mediante un canal de WhatsApp bajo el nombre de “Rinconia Nature”. Las estrategias mencionadas contribuyen al desarrollo del turismo local de manera innovadora. Para este estudio se utilizó un enfoque de investigación mixto, combinando métodos cuantitativos y cualitativos. También, se empleó un tipo de investigación descriptiva para entender la situación actual del problema y la exploratoria para descubrir aspectos nuevos. Aplica el método deductivo para formular y probar hipótesis a fin de optimizar la estrategia de Mobile Marketing para promover el patrimonio natural del Cantón Pasaje. Se concluye que existe una demanda de información sobre el patrimonio natural del Cantón Pasaje considerando las actividades al aire libre que se pueden realizar en él de forma sostenible y sustentable. Por esta razón, es importante destacar la necesidad de una estrategia de difusión efectiva donde el perfil demográfico de la muestra respalde el uso de Mobile Marketing. Cómo último, se recomienda desarrollar una aplicación móvil interactiva, integrar campañas publicitarias en Google AdWords y WhatsApp, además de producir contenido visual de alta calidad.
Keywords: DEMANDA; DISEÑO; MARKETING; PATRIMONIO NATURAL